THE USE OF ENVIRONMENTAL MANUFACTURING STRATEGY IN IMPROVING RESOURCE EFFICIENCY: A CASE STUDY OF WASIT TEXTILE AND SEWING FACTORY - Haider atta zabin (Jurnal Ekonomi, Bisnis dan Pendidikan, 2026)
Throughout the world, the manufacturing sector is facing growing pressure to find a balance between industrial productivity and environmental stewardship. Nonetheless, the pathways through which environmental manufacturing strategies lead to tangible benefits in resource efficiency are still poorly understood, especially in developing-country industrial settings. Abstract Objective: The study explores the relationship between environmental manufacturing strategy (EMS) and resource efficiency (RE) in textile manufacturing sector, with particular attention to the Wasit Textile and Sewing Factory in Iraq. We employed a quantitative, survey-based methodology. A well-structured questionnaire on a five-point Likert scale was used to conduct a field survey on 70 employees at administrative and technical levels and out of which 67 responses were returned useful, yielding a total response rate of 95.71 per cent. GPP and EDI: Two main Dimensions of EMS were treated as independent variables and RE including material, energy and water consumption: Dependent variable IBM SPSS Statistics version 26 was used to perform descriptive statistics, a Cronbach alpha reliability analysis, one-sample t-tests, Pearson correlation analysis and multiple regression modelling. Results indicate GPP (β = 0.521, p < 0.001) and EDI (β = 0.412, p < 0.001) both have statistically significant positive effects on RE and the model explains 71.0 per cent of the variance of RE (R² = 0.710) combined. The findings suggest factory management to institutionalise systematic environment practices and put in place investment contracts on cleaner production technologies and bio-design principles through the initial stages of the product development life cycle.